Attention-Related Brain Activation Is Altered in Older Adults With White Matter Hyperintensities Using Multi-Echo fMRI - Atwi, Sarah; Metcalfe, Arron W. S.; Robertson, Andrew D.; Rezmovitz, Jeremy; Anderson, Nicole D.; MacIntosh, Bradley J. (Frontiers in Neuroscience, 2018)
Cognitive decline is often undetectable in the early stages of accelerated vascular ageing. Attentional processes are particularly affected in older adults with white matter hyperintensities (WMH), although specific neurovascular mechanisms have not been elucidated. We aimed to identify differences in attention-related neurofunctional activation and behaviour between adults with and without WMH. Older adults with moderate to severe WMH (n=18, mean age=70 years), age-matched adults (n=28, mean age=72), and healthy younger adults (n=19, mean age=25) performed a modified flanker task during multi-echo blood oxygenation level dependent functional magnetic resonance imaging. Task-related activation was assessed using a weighted-echo approach. Healthy older adults had more widespread response and higher amplitude of activation compared to WMH adults in fronto-temporal and parietal cortices. Activation associated with processing speed was absent in the WMH group, suggesting attention-related activation deficits that may be a consequence of cerebral small vessel disease. WMH adults had greater executive contrast activation in the precuneous and posterior cingulate gyrus compared to HYA, despite no performance benefits, reinforcing the network dysfunction theory in WMH.